Isotope hydrology to provide insights into the behaviour of temporary wetlands as a basis for developing sustainable ecohydrological management strategies in Mediterranean regions. Issue 5 (9th March 2022) - Mattei, Alexandra; Huneau, Frédéric; Garel, Emilie; Sorba, Laurent; Orsini, Sophie; Santoni, Sébastien
Abstract: The lack of hydrological considerations in the existing protection statutes for small temporary wetlands has recently been pointed out as the main cause of their rapidly increasing disappearance. In the present study, we aim to demonstrate the interest of using the tools of isotope hydrology to obtain a rapid and cost effective understanding of the hydrological connectivity of Mediterranean temporary wetlands in order to define the optimal environmental conditions needed to ensure their sustainability. By combining physical and isotope measurements, we have investigated the fragile balance of direct precipitation, subsurface water and groundwater influencing the hydroperiod of a typical Mediterranean temporary pond. The use of the water stable isotopes enabled us to demonstrate (i) the major role played by groundwater and subsurface water in the flooding phase of the temporary pond; (ii) the involvement of different water reservoirs in varying proportions over time to maintain the pond filled with water: precipitation, subsurface and groundwater by using d‐excess; (iii) the main role played by evaporation in starting the drying up phase; and (iv) the connection existing between a geographically isolated wetland and the regional groundwater body. These results highlight the urgent need to consider both surface and groundwater fluxes in specific protection statutes for wetlands. To this end, we recommend the use of the water stable isotopes to provide insights into the hydrological behaviour of the wetlands in order to dispose of additional cost‐effective arbitration arguments to help ensure their sustainability. The lack of hydrological considerations in existing protection statutes for small temporary wetlands has recently been pointed out as the main cause of their disappearance. Here, by combining physical and isotopes measurements, we first highlight the main role played by groundwater in the flooding phase of the temporary pond and the involvement of different water reservoirs in varying proportions over time to maintain the pond filled. These results demonstrate the connection existing between a geographically isolated wetland and the regional groundwater and highlight the urgent need to consider both surface and groundwater fluxes in specific protection statutes for wetlands.